Bothersome Exposure to Online Sexual Content Among Adolescent Girls. (July 2015) - Ševcˇíková, Anna; Simon, Laura; Daneback, Kristian; Kvapilík, Tomáš
Prior research suggests that adolescent girls may react more negatively to online sexual content than boys. This study explored the qualitative experiences of adolescent girls who encountered bothersome or disturbing sexual content online. Fourteen girls (aged 15-17 years) were interviewed online about the context in which they saw bothersome sexual material and the reasons for their negative reactions. Results showed that participants felt bothered while using the Internet at home and in public, while engaging in online exploration, information seeking, or chatting with new acquaintances. Participants were also bothered when the sexual content portrayed sex of an extreme nature, seemed inappropriate for their age, broke norms for establishing romantic relationships, or threatened their home life. The impact of these experiences is discussed, especially in light of the participants' statements that they did not tell their parents or guardians about their experiences with bothersome online content.